Protocolo para condução de cadeira de rodas motorizada usando realidade virtual - Valentini, Caroline Araújo Marquez (2019)
The Assistive Technology (AT) equipment concession services of the Unified Health System and the centers responsible for the dispensing of such equipment, should consider eligibility criteria for motorized wheelchair prescription (PW), as well as perform training that guarantees security and autonomy for the users. Considerations punctuated in the legislation are gaps for the insertion of systematized protocols to follow the processes and services of AT. The use of technology without adequate training, in addition to contributing to the abandonment PW of the equipment, is a risk to the user and to the context in which this person performs tasks and activities. Difficulties such as crossing barriers, curving and resolving unforeseen situations require specific maneuvers in PW that can restrict social participation and reinsertion of the user in their daily occupations. Virtual Reality (VR) stands out as a solution because the disabled person is trained and adapted to technology in risk-free situations, transposing and improving skills in virtual environments that will later be incorporated into their daily context. This study selected 06 users of motorized wheelchair with spinal cord injury, aged 18 to 90 years, who met the eligibility criteria. An adapted protocol was developed with 12 functional tasks pertinent to conducting the real PW, for example: direct driving, maneuvering the chair between objects and making a left turn. Users conducted real PW without any previous training, simulating the therapeutic testing process performed at the CR. Then they underwent simulator training in virtual scenarios, which consisted of performing, once or twice a week, between 8 and 12 sessions for 3 months. Variables such as time to complete tasks, number of collisions and number of commands were collected. The objective was to evaluate the performance of the user in conducting PW after intervention in a VR environment. Tests were performed in order to compare the performance of the user in conducting the real PW before and after therapeutic intervention. VR training provided a reduction in the task time, in the number of collisions and in the number of commands in the ramp scenario for all users. Discrepancies in the performance of users in virtual scenarios pointed to a significant correlation between age and the collision variable. Suggestions for improving the simulator as a support tool were documented. Aspects of the perspective of training protocols pointed to relevance for the therapeutic practice.